"The Evils with Which We are Called to Grapple": Élite Reformers, Eugenicists, Environmental Psychologists, and the Construction of Toronto's Working-Class Boy Problem, 1860-1930 - Hogeveen, Brian (Labour/Le Travailleur, 2005)
Abstract Since the 19th century Toronto’s working-class bad boys have been subjected to intense scrutiny and control. The deviant and criminal conduct that brought working-class juvenile offenders to police and court attention did not change significantly over the late 19th and early 20th centuries. However, how their conduct was understood and governed was in a constant state of change and adjustment. This paper explores how Toronto’s working-class bad boys were represented and governed by élites, reformers, juvenile justice officials, medical experts, and university trained psychologists from 1860 to 1930. More specifically, it demonstrates how the 19th-century male juvenile offender, judged the product of injurious circumstances, was reinvented by eugenicists as the mentally deficient subject of the late 1910s and again (re)defined as an environmental psychiatric subject after 1925. These representations often overlapped, were discontinued, conflicted, and were in constant tension. Despite theoretical and practical differences, élites, eugenicists, and environmental psychologists were all particularly troubled by working-class male delinquency.